Некаталитический синтез аммиака - Юрченко, А. П.; Авина, Светлана Ивановна; Юрченко, А. А. (НТУ "ХПИ", 2008)
Розглянуто теоретичні засади, які покладені в основу нового способу синтезу аміаку. Запропонована технологія, яка суттєво відрізняється від традиційної. Вказані подальші напрями досліджень, що дозволять досягти повної адекватності усіх складових даної технології.

Theoretical principles which are fixed in basis of new method of synthesis of ammonia are considered – technology which substantially differs from standard is proposed. Further directions of researches which will permit to attain complete adequacy of all of constituents of this technology are indicated.
Keywords: азотные удобрения; атомарный водород; термическая диссоциация; тепловое воздействие; гидриды; газовая смесь